A framework to identify opportunities to address socioscientific issues in the elementary school curricula: A case study from England, Italy, and Portugal - Patrícia Pessoa; Joelyn de Lima; Valentina Piacentini; Giulia Realdon; Alex Jeffries; Lino Ometto; J. Bernardino Lopes; Dana L. Zeidler; Maria João Fonseca; Bruno Sousa; Alexandre Pinto; Xana Sá-Pinto (PLoS ONE, 2025)
Scientific literacy is crucial to address important and complex societal problems, both current and future. Teaching using a socioscientific issues (SSI) approach is a potential strategy to develop students’ scientific literacy, although teachers have reported concerns about its implementation, such as the inability to add additional distinct requirements to already demanding curricula. To facilitate this task, we describe the development of a valid and reliable instrument for curricula analysis, called “Framework for Identifying Opportunities to implement an SSI approach in science school curricula” (FIOSSI), and use it to identify opportunities to implement the SSI approach in the elementary school science curriculum of three European countries (England, Italy and Portugal). The framework categorizes SSI opportunities into three areas: 1) awareness of the issue; 2) socioscientific reasoning; and 3) socioscientific identity. Our analyses of the three countries’ elementary curricula reveal that the current versions have significant opportunities to explore awareness of SSI (especially relating to environmental and human health issues), promote the development of socioscientific reasoning, and foster socioscientific identity. FIOSSI can be a useful tool for education research and practice, and our results can help inform future research and guide educational policies.